(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2022)
Abstract This paper deals with applying statistical analysis of traffic safety to analyze the risks at level crossings. The social costs of railway accidents and traffic incidents at level crossings are very high and lead to a reduction in the levels of traffic safety. In addition to the consequences reflected in the loss of human lives, injuries, and disabilities, the stress and trauma of direct participants in traffic, accidents, and incidents at level crossings cause huge property and economic losses and significant primary and secondary traffic delays. The traffic safety analysis was conducted on 2128 level crossings, which are differently protected on the lines Joint Stock Company for Public Railway Infrastructure Management ”Serbian Railway Infrastructure” with statistical data of accidents in the Republic of Serbia from 2007 to 2017. The paper analyzes the obtained results using the methods of descriptive and inferential statistics to define measures of possible improvement of safety levels at the obtained critical level crossings. Also, a proposal was made for improving and raising the level of safety on level crossings through innovative education of direct participants in traffic.